2021
DOI: 10.1002/fsn3.2309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of onion on blood lipid profile: A meta‐analysis of randomized controlled trials

Abstract: Background Studies indicate that onion supplementation may be effective in the treatment of dyslipidemia; however, the results remain controversial. This meta‐analysis was conducted to evaluate potential benefits of onion on lipid profile. Methods Up to 12 October 2020, PubMed, Cochrane Library, Web of Science, and Scopus were searched for randomized controlled trials evaluating the effects of onion on lipid profile. Mean differences (MD) and 95% confidence intervals (CI) were calculated. Meta‐analysis was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…These could be attributed to its rich fibre and flavonoids (Hamauzu et al, 2011). Our result is consistent with the finding of Huang et al (2021) who reported that supplementation of onion has beneficial effect on dyslipidemia. It is evident from our finding that diet supplementation with onion could prevent atherosclerosis, a common feature of dioxin toxicity since according to Mattiuzzi et al (2020), controlling blood lipid decreases the risk of atherosclerosis and/or cardiovascular disease.…”
Section: Discussionsupporting
confidence: 92%
“…These could be attributed to its rich fibre and flavonoids (Hamauzu et al, 2011). Our result is consistent with the finding of Huang et al (2021) who reported that supplementation of onion has beneficial effect on dyslipidemia. It is evident from our finding that diet supplementation with onion could prevent atherosclerosis, a common feature of dioxin toxicity since according to Mattiuzzi et al (2020), controlling blood lipid decreases the risk of atherosclerosis and/or cardiovascular disease.…”
Section: Discussionsupporting
confidence: 92%
“…Cepa demonstrated potential benefits in maintaining the animal’s good health [ 67 ]. A study also reported that onion extract has blood lipid levels reducing potential [ 68 ]. Thus, we can conclude that Allium Cepa can efficiently decrease the health risk of cardiovascular events in both genders as it is rich in fiber and flavonoids [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%